Is the stellar initial mass function universal?. Issue 2 (April 2016) - Ferreras, Ignacio; La Barbera, Francesco; Vazdekis, Alexandre
Abstract : Ignacio Ferreras, Francesco La Barbera and Alexandre Vazdekis take a close look at one of the key ingredients in modelling star formation. Abstract : Ignacio Ferreras, Francesco La Barbera and Alexandre Vazdekis take a close look at one of the key ingredients in modelling star formation.